Ontology Conceptualization And Hadith Domain: A Systematic Literature Review - Noor Zytoon Mohamad Ismail; Siti Fatimah Mohd Tawil; Norzulaili Mohd Ghazali (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies